Development of Marketplace Product Data Mining and Analysis Application as a Reference in Running a Business - Joseph TN Wibawa; Randy Gunawan; Marchelleo Suhandi; Ricky Setiawan (President University, 2023)
Marketplaces has become the first choice as a third party that provides online selling and payment services that bridge sellers and buyers. The increasing need to shop in an efficient and convenient way has driven the popularity of using the marketplace. Moreover, with a variety of products and a fast transaction process, and more competitive prices, the use of the marketplace has shown significant growth in activity by the wider community. With the increasing use of marketplaces, data analysis from marketplaces is becoming a key element to understand market trends and make informed transaction decisions. Data analysis systems based on bot technology and Web-Scrapping libraries, such as Puppeteer, allow users to perform data analysis more efficiently and quickly, minimize the need for a data analysis team, and reduce time and costs. Given these factors, this research focuses on developing a web-based application that can analyze data coming from marketplaces and present it to users quickly and accurately.